Supervisi Manajerial Kepala Sekolah di SMP Darul Falah Batu Putuk Bandarlampung - Arinza Justistio; Amiruddin Amiruddin; Junaidah Junaidah (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2024)
This research was conducted to analyze the effectiveness of managerial supervision carried out by school principals with planning, implementation, coordination, evaluation and development of educational staff resources. Data was collected through in-depth interviews with school principals, TU heads, and operator staff, as well as direct observation in the field and analysis of related documents. The results of the research show that 1) The school principal's managerial supervision planning was carried out well by prioritizing the aspect of honesty, although managerial supervision activities had not been systematically programmed, but the goal setting to achieve the school's vision and mission was carried out well. 2) The school principal's coordination runs well through deliberation, especially coordinating with educational staff and coordinating with boarding school leaders 3). The implementation of the managerial supervision program is carried out with a flexible and spontaneous supervision period carried out with full discipline starting from the initial stage of implementation, the school principal coordinates and communicates with teaching and education staff to carry out supervision. 4) Evaluation of the managerial supervision program for the Principal of Darul Falah Middle School, Batu Putuk, Bandar Lampung, starting from formulating the objectives of the supervision evaluation. Data collection in the form of interviews, direct observations, reports and documentation was carried out professionally. And 5) The development of Human Resources (HR) for educational staff at Darul Falah Middle School in Batu Putuk Bandar Lampung is carried out starting with preparing a strategic plan for human resources for educational staff by organizing the assignment of educational staff based on their potential, recruiting educational staff in accordance with the analysis of school needs